Shaping elastic wavefront through zigzag-folded metasurfaces - Lin, Zhenkun; Tol, Serife (Frontiers in Physics, 2023)
We present a reconfigurable elastic metasurface design composed of an array of zigzag-folded sheets with parallel corrugations to control the wavefront of the refracted A 0 Lamb mode wave. The performance of this origami-inspired metasurface can be tuned by tailoring the thickness and folding angles of the sheets. Zigzag-folded sheets exhibit dynamic properties depending on their thicknesses and folding angles, yielding different phase profiles required for wavefront control via the metasurface. The transmission characteristics and phase modulation capability of the metasurface units are studied through numerical models and utilized to inform the metasurface design reconfiguring for different wave functions, such as wave focusing and deflecting at different frequencies. The design frameworks and the applicability of the reconfigurable metasurface are validated using a full-scale experimental setup. Overall, the proposed metasurface can accomplish distinct wavefront controls at adjustable geometrical parameters, developing new potentials for designing intelligent systems adaptable to different environments.